New records of deep-sea prawn of the genus Gennadas Spence Bate, 1881 (Crustacea: Decapoda: Benthesicymidae) from Southwestern Atlantic - Alves-Júnior, Flavio De Almeida; de Lemos, Rachel De Jesus Feio; Cardoso, Irene Azevedo; de Araújo, Marina De Sá Leitão Câmara; Bertrand, Arnaud; Souza-Filho, Jesser F. (Zootaxa, 2018)
Here, we report the new occurrences of four deep-water prawn of the genus Gennadas in the southwestern Atlantic: G. gilchristi recorded from the Mid-Atlantic Ridge region; G. capensis recorded from Brazilian waters off Fernando de Noronha Archipelago, Atol das Rocas and Ceará Chain; G. talismani and G. scutatus recorded both to Mid-Atlantic Ridge and to Brazilian waters.